Perpekstif Pendidikan tentang Beramal dengan Hadist Dhaif dan Hukumnya Menurut Para Ulama - Anis Amanulloh; Fahri Hidayat (Jurnal Ilmiah Edukatif, 2023)
This research examines the role and practice of the dhaif hadith in Islam, especially in the context of Islamic religious education. Hadith, as the second source of law after the Koran, has an essential function in providing explanations (bayan) of the teachings of the Koran. This research uses a qualitative approach by reviewing literature from the opinions of ulama. The results of this research state that there are two main approaches to dhaif hadith. Some scholars think that dhaif hadith should be avoided and not practiced in any form, considering its weakness in the chain of transmission and the potential for error. Meanwhile, other groups of ulama allow the use of dhaif hadith, especially in the context of fadha'ilul a'mal (the importance of charity), as long as it does not conflict with the teachings of the Koran and stronger hadith. This research highlights the differences in these approaches and their impact on the practice of Islamic education. These findings are essential for educators and researchers in Islamic Religious Education to understand how dhaif hadith can or cannot be integrated into religious teaching and practice. This research also provides insight into the flexibility of interpretation in Islam and how this influences a dynamic and contextual approach to religious education.